PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS VIDEO PADA MATERI TEKNIK DASAR PASSING BOLA VOLI DI MTS AR-RAHMAN PALEMBANG - Wijaya, Azhar Hanif (Pendidikan Jasmani, Kesehatan, dan Rekreasi, 2021)
Research methods can be classified based on the purpose and level of naturalness of the object under study. The type of this research is Research and Development.